INFLUENCE OF COMPETENCE, MOTIVATION AND DISCIPLINE ON PDAM EMPLOYEE PERFORMANCE IN SOUTH SUMATRA PROVINCE BANYUASIN DISTRICT - Mandy Okmyarti Pratiwi; Sa'adah Siddik; Choiriyah Choiriyah (KOLEGIAL, 2020)
This study aims to determine the effect of competency, motivation and discipline together and partially on Employee Performance in the Province of South Sumatra. The design of this research is associative research by connecting between independent and dependent variables. The data used in this study were primary and secondary data, and respondents' answers were as many as 182 study samples of PDAM employees in South Sumatra Province. The analytical method used is multiple linear regression and through testing the validity and reliability. Test data used to determine the characteristics of the data are the normality test and linearity test. The test model used consists of multicollinearity and linearity tests, assisted by SPSS for windows analysis tool with a significant level of α is 0.05.The results of multiple linear regression testing show competence, motivation and discipline together have a positive and significant effect on employee performance. Competence, motivation and discipline partially have a positive and significant effect on employee performance.